Workshop Characteristics Related to Chronic Disease Self-Management Education (CDSME) Program Attendance - Matthew Lee eSmith; Marcia Gail Ory; Luohua eJiang; Kate eLorig; Kristie eKulinski; SangNam eAhn; SangNam eAhn (Frontiers Media S.A., 2015)
*